On the Relationship Between Regions of Large-Scale Field-Aligned Currents and Regions of Plateau in Plasma Pressure Observed in the Equatorial Plane of the Earth S Magnetosphere - Stepanova, M (John Wiley and Sons Inc, 2023)
Since the discovery of the large-scale field-aligned currents it is widely acknowledged that gaps exist between the Region 1 (R1) and Region 2 (R2) currents in which the current values are relatively small as compared to neighboring regions. Assuming that the field-aligned currents are generated by plasma pressure gradients, we analyzed data collected by the THEMIS satellites between 2007 and 2011 to identify regions with very low plasma pressure gradients (pressure plateaus), which could be responsible for the appearance of these gaps. It was found that the pressure profiles with low radial gradients are typically located between 8 and 10 Radii around the Earth. Projections of pressure plateau regions onto ionospheric altitudes, for both individual events and on a statistical basis, coincide with the locations of gaps between Iijima and Potemra field-aligned currents. The role played by identified pressure plateaus in shaping the pattern of large-scale field-aligned currents is discussed. © 2023. The Authors.